What Do Secondary Schools Need to Create Healthier Canteens? The Development of an Implementation Plan - Evenhuis, Irma J.; Vyth, Ellis L.; Nassau, Femke van; Veldhuis, Lydian; Westerman, Marjan J.; Seidell, Jacob C.; Renders, Carry M. (Frontiers in Public Health, 2021)
Introduction: The Netherlands Nutrition Centre developed guidelines to improve the availability and accessibility of healthier food products in Dutch canteens. This paper describes the development of an implementation plan to facilitate implementation of Guidelines for Healthier Canteens in Dutch secondary schools. Materials and methods: In cooperation with stakeholders (i.e., school/caterer managers/employees, school canteen advisors, researchers) and based on theory, we developed an implementation plan in three steps. First, we identified factors that impede/facilitate stakeholders to create a healthier school canteen during 14 interviews. Second, 25 experts discussed and prioritized these identified factors in an expert meeting. Third, we translated these factors into tools to be included in the implementation plan, by making use of behavior change taxonomies and evidence-based implementation strategies. Results: The plan aims to support stakeholders in implementing healthier school canteens and consists of five tools: 1) tailored advice based on an online questionnaire to assess schools’ and stakeholders’ context and the Canteen Scan (i.e. an online tool to assess the availability and accessibility of food/drink products); 2) communication materials with information and examples; 3) online community for support by sharing experiences/questions; 4) digital newsletter as reminder/support; 5) fact sheet with students’ needs/wishes to tailor the canteen. Discussion: This study illustrates how collaboration between science, policy and practice resulted in a tailored implementation plan aimed to support schools to adhere to school canteen policy. This development serves as a good example for researchers, health promotion policymakers, and practitioners how to create an implementation plan that fits the needs of stakeholders.